Training Using Simulation in Internal Medicine Residencies: An Educational Perspective. (March 2015) - Flannery, Michael T.; Villarreal, Kara F.
Abstract: Background: The American Board of Internal Medicine has defined through the min-CEX (Clinical Examination booklet) that a resident would need to perform anywhere from 3 to 5 procedures to be competent in a given procedure. Many faculty and residents believe that this number is too low to achieve competency. Methods: Although simulation has been required as part of medical training, we have reviewed a number of articles addressing competence and potentially fewer complications with improved patient safety. Results: The Accreditation Council for Graduate Medical Education has simply stated that simulation should be part of residency training. However, this has resulted in a disorganized approach among the nearly 385 internal medicine programs in the United States. Conclusions: This article suggests a model of simulation that addresses procedures, medical codes and major medical problems that each resident achieve competence in before graduating residency. This would require minimally a doubling of the number of procedures to define competency and will do so in a far more scientific method.